DECODING GRATITUDE AT WORK: A STUDY OF KRTAJJATA IN INDIAN ORGANIZATIONAL SETTINGS - Banerjee, Anindita; Bhalerao, Hemangi; Ali, Afsar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The concept of gratitude within workplace settings has been extensively examined in Western organisational behaviour studies; nonetheless, the cultural nuances of gratitude have yet to be thoroughly theorised. This conceptual paper presents and examines kRtajJatA, an indigenous rather Bhartiya construct of gratitude, as a distinctive framework for understanding employee attitudes and behaviours within Indian organisational contexts. Grounded in the principles of Sanskrit philosophy and the values of Indian culture, kRtajJatA transcends mere gratitude, incorporating elements of moral duty, mutual respect, and emotional balance within society. The study rigorously analyses current gratitude frameworks and situates kRtajJatA from the Indian Knowledge System within the Asian socio-cultural landscape. This framework connects kRtajJatA with various workplace outcomes, including organisational citizenship behaviour (OCB), employee engagement, and job satisfaction. This study enhances organisational theory by integrating indigenous psychology and contextual sensitivity, advocating for empirical validation in subsequent investigations. The paper highlights the importance of culturally grounded construct for advancing organizational practices in India and similar collectivist cultures.